2010
DOI: 10.3109/13880200903222952
|View full text |Cite
|
Sign up to set email alerts
|

A study of the larvicidal activity of twoCrotonspecies from northeastern Brazil againstAedes aegypti

Abstract: The essential oils of Croton heliotropiifolius Kunth (Euphorbiaceae) and Croton pulegiodorus Baill. were selected for larvicidal evaluation against Aedes aegypti L. (Diptera: Culicidae) and studied qualitatively and quantitatively by GC and GC-MS. Sixty-one compounds representing 92.03% (C. heliotropiifolius) and 85.68% (C. pulegiodorus) of the essential oils, respectively, have been identified. The major components of C. heliotropiifolius essential oil were identified as beta-caryophyllene (35.82%), bicycloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 20 publications
4
33
0
2
Order By: Relevance
“…Among the major components, only β-caryophyllene and patchoulol, which were found in different proportions in stem, flower, and leaf oils, and it demonstrated acaricidal activity. The biological properties of β-caryophyllene have been confirmed in previous reports involving the larvae of Aedes aegypti (Diptera: Culicidae) (Dória et al, 2010) and T. urticae (Araújo et al, 2012). Moreover, the major constituents are not the only components responsible for the fumigating action observed in the experiments and it is likely that these compounds act in synergy with those found in smaller amounts .…”
Section: Discussionsupporting
confidence: 82%
“…Among the major components, only β-caryophyllene and patchoulol, which were found in different proportions in stem, flower, and leaf oils, and it demonstrated acaricidal activity. The biological properties of β-caryophyllene have been confirmed in previous reports involving the larvae of Aedes aegypti (Diptera: Culicidae) (Dória et al, 2010) and T. urticae (Araújo et al, 2012). Moreover, the major constituents are not the only components responsible for the fumigating action observed in the experiments and it is likely that these compounds act in synergy with those found in smaller amounts .…”
Section: Discussionsupporting
confidence: 82%
“…Bitter orange essential oil exhibited limonene (90.78%) and myrcene (3.87%) as main compounds. According to Dória et al (2010), "velaminho" essential oil had β-caryophyllene (20.96%), bicyclogermacrene (16.89%), and germacrene D (10.55%) as major components. d) Fumigation -to evaluate the fumigant effect, glass containers (bomboniere) were used as fumigation chambers (1 L), where 10 R. dominica adults were confined.…”
Section: Methodsmentioning
confidence: 99%
“…The leaves and bark are used either as infusions or pills for the treatment of gastrointestinal disturbances and weight loss (Govaerts et al, 2000). The essential oil of C. heliotropiifolius presented a significant larvicidal activity against Aedes aegypti (Doria et al, 2010) while the ethanolic extract demonstrated an interesting insecticidal activity against Sitophilus zeamais (Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%